COMPARISON BETWEEN BASEMENT DEPTHS ESTIMATED FROM LAND MAGNETIC AND AEROMAGNETIC SURVEYS, WEST IRAQ - Al-Mashaekhy, Dhiya (Iraqi Journal of Science, 2024)
Basement depth is determined from land magnetic survey along a traverse with a length of 190 Km in the western desert of Iraq. The traverse was extended from Akkashat to Um Rthuma area. The shape and depth of the basement surface is obtained through using Geomodel program. The outcome is compared with the basement depth detrmined by Compagine Generale de Geophysique (CGG), through using aeromagnetic data. There are certain variations between the two results concerning the depth values along the traverse profile. The CGG basement depth map provided a general picture and the present results indicate the importance of re-determination of basement depth from field data and use the developed and sophisticated analysis procedures to get a new look to such important topic.